Observed discriminability is more variable than predicted by signal detection theory. (January 2020) - Hautus, M.J.; van Hout, D.; Lee, H.-S.; Stocks, M.A.; Shepherd, D.
Highlights: Compared variation in replicated performance across four difference tests. Employed A-Not A, 2-AFC and their reminder versions (A-Not AR and 2-AFCR). A-Not A had higher variability than the other tasks. 2-AFC and 2-AFCR had lower performance that the other tasks. 2-AFC and 2-AFCR had the lowest variation in replicated performance. Abstract: Food scientists and technologists are interested in how sensitive judges and consumers are to changes in product formulations. Numerous approaches to measuring sensitivity have developed at a rapid rate in the last 25 years, however, the evaluation and assessment of sensory tasks is still ongoing. The current study compared the efficiency of four difference tests (A-Not A, A-Not AR, 2-AFC, 2-AFCR) across three concentrations (difficulty levels) of orange essence. To determine which of the four tasks had the lowest variance in d ′, the decision strategy used by the judges first had to be ascertained. Using the rating-scale approach of signal detection theory, four estimates of sensitivity, d ′, were obtained for each judge ( n  = 10) at each of the three difficulty levels, for all four tasks. Results indicate that the majority of judges adopted the β-strategy for the A-Not A and A-Not AR tasks, and the β/τ-strategy for the 2-AFC and 2-AFCR tasks. The A-Not A and A-Not AR tasks produced greater estimates of d ′ than the other two tasks, and the A-Not A task exhibited a greater variance in d ′ than the other three tasks.